The Increased Satisfaction of Customer Loyalty: An Impact of Variety Seeking Moderation - Agustinus Numberi, Victor Pattiasina, Eduard Yohannis Tamaela (International Journal of Advanced Science and Technology, 2020)
This study was conducted in Indonesia. It is included as analytical research that conducted at salons registered with the Jayapura City Regional Revenue Service. Through a survey using a questionnaire instrument for data collection and a non-probability sampling method with a purposive sampling technique for sample selection, we obtained a sample of 200 customers. The results showed that customer satisfaction has a positive influence on customer loyalty, and it is evident that variety-seeking moderates the effect of customer satisfaction on customer loyalty of salon services in Jayapura City- Indonesia.